Śmierć to dialog. Edgar Allan Poe, Emily Dickinson i "podchodzenie śmierci". - Sławek, Tadeusz (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
The essay is an attempt at reading a story by Edgar Allan Poe and a poem by Emily Dickinson in order to investigate the way in which death makes its inroads into the domain of life. Poe’s text demonstrates that only through a thoughtful and careful incorporation of death into the biological matter of life can we resist, in a sensible way, death’s incursions which threaten our existence. Dickinson conveys the same message in different terms, i.e. between “Dust” and “Spirit”, as well as between the threat of dissolution (“Dissolve”) and the reassurance of “Trust”. A dialogue takes place here through which death presents itself in the house of life. It dwells within a person’s being, which now reveals itself as a constant exchange between the body and the soul. In order not to make this exchange a symptom of life-in-decline (which is a reference to Jan Patočka’s conceptmof civilization as waning, i.e. a kind of waning which he renders in the Czech languageas úpadková), a force has to operate within it which resists the temptation of both sides to demonstrate its supposedly unquestionable right towards the truth.